Reconstruction of the time-dependent electronic wave packet arising from molecular autoionization - Bello, Roger Y.; Canton, Sophie E.; Jelovina, Denis; Bozek, John D.; Rude, Bruce; Smirnova, Olga; Ivanov, Mikhail Y.; Palacios, Alicia; Martin, Fernando (Science Advances, 2018)
Autoionizing resonances are paradigmatic examples of two-path wave interferences between direct photoionization, which takes a few attoseconds, and ionization via quasi-bound states, which takes much longer. Time-resolving the evolution of these interferences has been a long-standing goal, achieved recently in the helium atom owing to progress in attosecond technologies. However, already for the hydrogen molecule, similar time imaging has remained beyond reach due to the complex interplay between fast nuclear and electronic motions. We show how vibrationally resolved photoelectron spectra of H2 allow one to reconstruct the associated subfemtosecond autoionization dynamics by using the ultrafast nuclear dynamics as an internal clock, thus forgoing ultrashort pulses. Our procedure should be general for autoionization dynamics in molecules containing light nuclei, which are ubiquitous in chemistry and biology.
CRIS-Team Scopus Importer:2023-04-20